The Potential of Black Cumin (Nigella sativa, L.) Seeds Extract to Prevent Polyphagia and Weight Loss in Rattus Norvegicus of Diabetes Mellitus-Type 2 - Susilowati, Retno; Ghazali, Ahmad; Aâ€™yunin, Nabila Qurrota (El-Hayah : Jurnal Biologi, 2019)
Patients of Diabetes Mellitus-type 2 (DM-2) is not only characterized by an increase of blood glucose levels, but also it is characterized by polyphagia and weight loss. This research aimed to discover the potential of 80% ethanol extract of Indonesia Nigella sativa L. (black cumin) seeds to the feed consumption level and changes in body weight of DM-2 rats model due to the administration of High Fat Diet (HFD) followed by the induction of streptozotocin (STZ) in a dose of 30 mg/kg Body Weight (BW). The DM-2 rats as the induction results divided into five groups, it was given a treatment using N. sativa extract with different doses, i.e. 0, 24, 48 and 72 mg/kg BW (DM-0, DM-24, DM-48, DM-72), positive control used metformin 45 mg/kg BW (DM-Metf). Non-DM rats (Normal)Â  used as reasonable control. HFD induction carried out for 14 weeks, and N. sativa therapy conducted for four weeks after the oral glucose tolerance test. During the treatment, an observation of the feed consumption level and weekly weight gain were carried out. The data obtained were tested using one-way ANOVA, and it continued by Duncan Multiple Rank Test (DMRT), Î±= 5%. The research results indicated that the administration of 80% ethanol extract Indonesia N. sativa using the doses of 24 mg/kg BW and 48 mg/kg BW can control the feed consumption levels and prevent significant weight loss (p0.05)